Influence of pellet size on growth performance in nursery pigs and growth performance, nutrient digestibility, and stomach morphology in finishing pigs - S L Traylor; Keith C Behnke; P Sorrell; Fred J Fairchild; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1996)
Pellet size (i.e., 3/32 in., 5/32 in., 5/16 in., and 1/2 in. diameter) had little effect on growth performance during the early stages (d 0 to 5) of the nursery phase. However, the 5/32 in. diameter pellets supported the best efficiencies of gain during the overall nursery (d Â°to 29) and finishing phases.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Nursery pigs; Finishing pigs; Pellet size; Growth